Attitude towards active surveillance: a cross-sectional survey among patients with uroandrological disorders. Issue 8 (29th August 2018) - Capogrosso, Paolo; Boeri, Luca; Ventimiglia, Eugenio; Camozzi, Ilenya; Cazzaniga, Walter; Chierigo, Francesco; Scano, Roberta; Briganti, Alberto; Montorsi, Francesco; Salonia, Andrea
Abstract : Objectives: We looked at subjective attitude towards active surveillance (AS) as the first option for cancer management in a cohort of patients seeking first medical help for uroandrological disorders prior to a formal discussion with a caregiver. Design: Cross-sectional observational study. Setting: Uroandrological outpatient clinic of a European academic centre. Participants: Data of 1059 patients at their first access for uroandrological purposes from January 2014 to December 2016 were analysed. Intervention: Patients were invited to complete a survey with closed questions investigating their attitude towards AS, prior to any clinical evaluation. Likewise, patients were invited to score the importance given to different aspects of personal life in the case of a cancer diagnosis, using a 10-point Likert scale. Primary and secondary outcomes measures: The reported opinion towards AS management for cancer was assessed. Logistic regression analyses tested participants' sociodemographic characteristics associated with a positive opinion on AS. Results: Positive, negative and doubtful attitudes towards AS were observed in 347 (33%), 331 (31%) and 381 (36%) patients, respectively. Female patients were more likely to report a negative attitude towards AS (38.7% vs 29.6%, p=0.04) while patients with previous parenthood more frequently reported a positive opinion on AS (37.2% vs 29.9%, p=0.005). Patient age emerged as the only predictor of a positive attitude towards AS (OR 1.03; 95% CI 1.01 to 1.04, p<0.001), with a 46% and 33% probability of being pro-AS for a patient aged 65 and 45 years, respectively. Conclusions: One out of three patients would express positive feedbacks on AS in the unfortunate case of tumour diagnosis, only according to his/her baseline personal opinion and prior to any discussion with a cancer caregiver. The older the patient, the higher the probability of being compliant with a conservative management for cancer.